Using the Problem-Based Learning Model on Students' Argumentation Writing Motivation - Haryanti, Ade Siti; Samosir, Astuti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research is to find out how the use of the problem besad learning models affects the motivation to write argements at Indraprasta PGRI University students. The method use in the research is an experimental method with a research sampel of 40 students. Devided into two classes, namely experimental class with 20 students in a each class. The results of the research are that there is a significant influence of the use on the problem besad learning on the motivation to write argument at Indraprasta PGRI University students. This is besad on the hypothesis testing with a significance level 5%, obtained tcount> ttable (6,78 > 2,03), so H1 is this rejected and H1 is accepted. In this way, the hypothesis is the tested and significantly accepted. There for, it can be concluded that there is a influence of using the problem besad learning model on the student motivation tp write arguments and the average motivation to write argument using the problem besad learning model is 78 higher than that using the conventional learning model of 69.